Staphylococcus aureus bacteremia and recurrent staphylococcal infection in patients with acquired immunodeficiency syndrome and aids-related complex - Jacobson, Mark A.; Gellermann, Holger; Chambers, Henry (The American journal of medicine, 1988)
An increased incidence of Staphylococcus aureus bacteremia has recently been described in patients with the acquired immunodeficiency syndrome (AIDS). However, other risk factors for community-acquired S. aureus bacteremia (including intravenous drug abuse and lymphedema) were present in nearly all these AIDS-related cases of S. aureus infection. Our purpose was to review cases of S. aureus bacteremia that occurred in patients with AIDS or AIDS-related complex (ARC) who did not have a recent history of intravenous drug use, lymphatic obstruction, or neutropenia. Patients at San Francisco General Hospital between October 1984 and October 1987 with blood culture results positive for S. aureus were identified. A review of this group revealed 22 cases of S. aureus bacteremia that occurred in 18 patients with an underlying diagnosis of AIDS or ARC, none of whom had a recent history of intravenous drug use, lymphedema secondary to Kaposi's sarcoma, or neutropenia. An intravenous catheter was the single most important risk factor for S. aureus bacteremia and was identified as the source for bacteremia in 16 (73 percent) of the 22 episodes. Based on 1986 outpatient clinic records, we calculated an incidence of S. aureus bacteremia occurring in nonintravenous-drug-using male AIDS or ARC patients, 18 to 44 years old, that was 5.4 episodes/1,000 patients. Although the mean duration of appropriate antibiotic therapy was 18 days, late metastatic complications of S. aureus bacteremia occurred in six (35 percent) of 17 AIDS/ARC patients who survived initial antibiotic therapy. Non-intravenous-drug-using AIDS and ARC patients (especially those with indwelling venous catheters) appear to be at high risk for S. aureus bacteremia, with a higher late metastatic complication rate than that reported for recent historical control subjects.